Autologous Periosteum-Derived Micrografts and PLGA/HA Enhance the Bone Formation in Sinus Lift Augmentation - Rodriguez y Baena, Ruggero; D'Aquino, Riccardo; Graziano, Antonio; Trovato, Letizia; Aloise, Antonio C.; Ceccarelli, Gabriele; Cusella, Gabriella; Pelegrine, André A.; Lupi, Saturnino M. (Frontiers in Cell and Developmental Biology, 2017)
Sinus lift augmentation is a procedure required for the placement of a dental implant, whose success can be limited by the quantity or quality of available bone. To this purpose, the first aim of the current study was to evaluate the ability of autologous periosteum-derived micrografts and Poly(lactic-co-glycolic acid) (PLGA) supplemented with hydroxyl apatite (HA) to induce bone augmentation in the sinus lift procedure. Secondly, we compared the micrograft's behavior with respect to biomaterial alone, including Bio-Oss® and PLGA/HA, commercially named Alos. Sinus lift procedure was performed on 24 patients who required dental implants and who, according to the study design and procedure performed, were divided into three groups: group A (Alos + periosteum-derived micrografts); group B (Alos alone); and group C (Bio-Oss® alone). Briefly, in group A, a small piece of periosteum was collected from each patient and mechanically disaggregated by Rigenera® protocol using the Rigeneracons medical device. This protocol allowed for the obtainment of autologous micrografts, which in turn were used to soak the Alos scaffold. At 6 months after the sinus lift procedure and before the installation of dental implants, histological and radiographic evaluations in all three groups were performed. In group A, where sinus lift augmentation was performed using periosteum-derived micrografts and Alos, the bone regeneration was much faster than in the control groups where it was performed with Alos or Bio-Oss® alone (groups B and C, respectively). In addition, the radiographic evaluation in the patients of group A showed a radio-opacity after 4 months, while after 6 months, the prosthetic rehabilitation was improved and was maintained after 2 years post-surgery. In summary, we report on the efficacy of periosteum-derived micrografts and Alos to augment sinus lift in patients requiring dental implants. This efficacy is supported by an increased percentage of vital mineralized tisssue in the group treated with both periosteum-derived micrografts and Alos, with respect to the control group of Alos or Bio-Oss® alone, as confirmed by histological analysis and radiographic evaluations at 6 months from treatment.